Higher SARS-CoV-2 seroprevalence in workers with lower socioeconomic status in Cape Town, South Africa. - Jane Alexandra Shaw; Maynard Meiring; Tracy Cummins; Novel N Chegou; Conita Claassen; Nelita Du Plessis; Marika Flinn; Andriette Hiemstra; Léanie Kleynhans; Vinzeigh Leukes; Andre G Loxton; Candice MacDonald; et al. (PLoS ONE, 2021)
Background Inequality is rife throughout South Africa. The first wave of COVID-19 may have affected people in lower socioeconomic groups worse than the affluent. The SARS-CoV-2 seroprevalence and the specificity of anti-SARS-CoV-2 antibody tests in South Africa is not known. Methods We tested 405 volunteers representing all socioeconomic strata from the workforce of a popular shopping and tourist complex in central Cape Town with the Abbott SARS-CoV-2 IgG assay. We assessed the association between antibody positivity and COVID-19 symptom status, medical history, and sociodemographic variables. We tested 137 serum samples from healthy controls collected in Cape Town prior to the COVID-19 pandemic, to confirm the specificity of the assay in the local population. Results Of the 405 volunteers tested one month after the first peak of the epidemic in Cape Town, 96(23.7%) were SARS-CoV-2 IgG positive. Of those who tested positive, 46(47.9%) reported no symptoms of COVID-19 in the previous 6 months. Seropositivity was significantly associated with living in informal housing, residing in a subdistrict with low income-per household, and having a low-earning occupation. The specificity of the assay was 98.54%(95%CI 94.82%-99.82%) in the pre-COVID controls. Conclusions There is a high background seroprevalence in Cape Town, particularly in people of lower socioeconomic status. Almost half of cases are asymptomatic, and therefore undiagnosed by local testing strategies. These results cannot be explained by low assay specificity.